Voices emerging from the shadows: Radiologic practitioners' experiences of challenging conversations. Issue 1 (January 2017) - Meyer, Elaine C.; Lamiani, Giulia; Luff, Donna; Brown, Stephen D.
Highlights: Radiologic practitioners face greater expectations for direct patient communication. Conveying serious news is the most common of challenging radiologic conversations. Inexperience and gaps in communication education hamper radiologic practitioners. Clinical uncertainty poses communicative challenges for radiologic practitioners. Interprofessional radiologic teamwork amplifies communicative demands. Abstract: Objective: Traditionally, radiologists have practiced their profession behind the scenes. Today, radiologic practitioners face mounting expectations to communicate more directly with patients. However, their experiences with patient communication are not well understood. The aim of this study was to describe the challenges of radiologic practitioners when communicating with patients. Methods: Twelve day-long interprofessional communication skills workshops for radiologic clinicians were held at Boston Children's Hospital. Prior to each workshop, participants were asked to write narratives describing experiences with difficult radiologic conversations that they found particularly challenging or satisfying. The narratives were transcribed and analyzed through thematic content analysis by two researchers. Results: Radiologists, radiology trainees, technologists, nurses, and medical interpreters completed 92 narratives. The most challenging aspects of healthcare conversations included: Conveying Serious News (n = 44/92; 48%); Expanded Scope of Radiologic Practice (n = 37/92; 40%); Inexperience and Gaps in Education (n = 15/92; 16%); Clinical Uncertainty (n = 14/92; 15%); and Interprofessional Teamwork (n = 9/92; 10%). Conclusion: Radiologic clinicians face substantial communicative challenges focused on conveying serious, unexpected and uncertain diagnoses amid practical challenges and limited educational opportunities. Practice implications: Innovative educational curricula that address these challenges may enhance radiologic practitioners' success in adopting patient-centered communication.